Characterization of Lgr6+ Cells as an Enriched Population of Hair Cell Progenitors Compared to Lgr5+ Cells for Hair Cell Generation in the Neonatal Mouse Cochlea - Zhang, Yanping; Guo, Luo; Lu, Xiaoling; Cheng, Cheng; Sun, Shan; Li, Wen; Zhao, Liping; Lai, Chuijin; Zhang, Shasha; Yu, Chenjie; Tang, Mingliang; Chen, Yan; et al. (Frontiers in Molecular Neuroscience, 2018)
Hair cell (HC) loss is irreversible because only very limited HC regeneration has been observed in the adult mammalian cochlea. Wnt/β-catenin signaling regulates prosensory cell proliferation and differentiation during cochlear development, and Wnt activation promotes the proliferation of Lgr5+ cochlear HC progenitors in newborn mice. Similar to Lgr5, Lgr6 is also a Wnt downstream target gene. Lgr6 is reported to be present in adult stem cells in the skin, nail, tongue, lung, and mammary gland, and this protein is very important for adult stem cell maintenance in rapidly proliferating organs. Our previous studies showed that Lgr6+ cells are a subpopulation of Lgr5+ progenitor cells and that both Lgr6+ and Lgr5+ progenitors can generate Myosin7a+ HCs in vitro. Thus we hypothesized that Lgr6+ cells are an enriched population of cochlear progenitor cells. However, the detailed distinctions between the Lgr5+ and Lgr6+ progenitors are unclear. Here, we systematically compared the proliferation, HC differentiation, and detailed transcriptome expression profiles of these two progenitor populations. We found that the same number of isolated Lgr6+ progenitors generated significantly more Myosin7a+ HCs compared to Lgr5+ progenitors; however, Lgr5+ progenitors formed more epithelial colonies and more spheres than Lgr6+ progenitors in vitro. Using RNA-Seq, we compared the transcriptome differences between Lgr5+ and Lgr6+ progenitors and identified a list of significantly differential expressed genes that might regulate the proliferation and differentiation of these HC progenitors, including 4 cell cycle genes, 9 cell signaling pathway genes, and 54 transcription factors. In conclusion, we demonstrate that Lgr6+ progenitors are an enriched population of inner ear progenitors that generate more HCs compared to Lgr5+ progenitors in the newborn mouse cochlea, and the our research provides a series of genes that might regulate the proliferation of progenitors and HC generation.